Food security and its determinants among rural households: A case study in Buwenge eastern Uganda - Kalinaki Hanifar; Martianto Drajat; Riyadi Hadi (BIO Web of Conferences)
Uganda’s population still faces food insecurity, with rural areas disproportionately affected. Rural areas in Eastern Uganda are still threatened by food insecurity. However, there is still insufficient documentation on food security and factors influencing it at the household level in Buwenge, Eastern Uganda. This study aimed to determine the level of food security and its determinants among rural households where food insecurity remains prevalent despite governmental efforts. A cross-sectional, quantitative study involving 250 households was conducted between January and March 2024. Data were collected through systematically sampled, verbally administered questionnaires, assessing food security levels using the Household Food Insecurity Access Scale (HFIAS). Results showed that 90.4% of households faced food insecurity, with 29% severely food insecure. Socio-economic determinants included the age, gender, and marital status of the household head, land availability, and health status. Younger and female-headed households, larger families, and households with limited land access faced higher risks of food insecurity. Additional risk factors impacting food security included reliance on market purchases alone, inadequate food safety, insufficient post-harvest handling techniques, lack of safe water, and engagement in sugarcane monoculture. Households practicing modern post-harvest methods, adequate waste management, and safe water access were more likely to achieve food security.